2015
DOI: 10.3109/0886022x.2015.1007805
|View full text |Cite
|
Sign up to set email alerts
|

Donor kidney glomerular filtration rate and donor/recipient body surface area ratio influence graft function in living related kidney transplantation

Abstract: Both SKGFR and D/R BSA ratio should be considered for choosing potential living related donors. Donors with SKGFR < 40 mL/min and D/R BSA ratio ≤ 0.8 should be carefully selected. Satisfactory graft function in donors with SKGFR < 40 ml could be achieved if their D/R BSA ratio is >0.8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…GFR rate was estimated using the novel Chronic Kidney Disease-Epidemiology Collaboration equation based on sCr [13,14] . All the donors and recipients' BSAs were estimated by the formula of Mosteller [15,16] Variables related with the presence of simple renal cysts by means of above analysis (p < 0.2) were included in the multivariate logistic regression model in forward stepwise fashion, to confirm independent predictive factors of renal cyst formation. Variance inflation factors (VIF) were calculated to check for collinearity; VIF value >10 meant serious collinearity between the variables.…”
Section: Auxiliary Examination Information and Statistical Analysismentioning
confidence: 99%
“…GFR rate was estimated using the novel Chronic Kidney Disease-Epidemiology Collaboration equation based on sCr [13,14] . All the donors and recipients' BSAs were estimated by the formula of Mosteller [15,16] Variables related with the presence of simple renal cysts by means of above analysis (p < 0.2) were included in the multivariate logistic regression model in forward stepwise fashion, to confirm independent predictive factors of renal cyst formation. Variance inflation factors (VIF) were calculated to check for collinearity; VIF value >10 meant serious collinearity between the variables.…”
Section: Auxiliary Examination Information and Statistical Analysismentioning
confidence: 99%
“…When HLA mismatch number were different among multiple donors, we selected the donor with the smallest number of HLA mismatch (n = 10). Donor /recipient BSA ratio is a reliable indicator of nephron dosing 13 . Donor/recipient BSA ratio > 1.3 was a contraindication to kidney transplantation in our center.…”
Section: Resultsmentioning
confidence: 99%
“…The underlining challenge in such patients with extreme stature is to ensure that the physiological capacity and the functioning nephron mass of the donor organ can meet the increased metabolic needs of this unique recipients so to alleviate their need for renal replacement therapy and have a significant positive impact on their overall health, quality of life, and life expectancy. Recent studies have confirmed that the graft kidney volume/recipient BSA ratio along with the donor age and recipient’s gender are independent predictors of recipient GFR in the early post-transplant period[ 4 - 6 ]. Considering the above concern, the option of synchronous dual deceased kidney transplantation in such extreme stature patients seems reasonable and needs to be considered at the time of wait listing them for a deceased donor kidney transplant and weighted against depriving the second graft from another potential recipient given the current scarcity of deceased donor organs.…”
Section: Discussionmentioning
confidence: 99%